2023
DOI: 10.1038/s41598-023-32774-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FIFA 11 + warm-up program on kinematics and proprioception in adolescent soccer players: a parallel‑group randomized control trial

Abstract: This study aimed to compare the effects of 8 weeks 11 + warm-up injury prevention program on kinematics and proprioception in adolescent male and female soccer players. Forty adolescent soccer players (20 males, 20 females) aged between 14–16 years old were randomly assigned into four groups. The experimental group performed the 11 + program for 8 weeks and the control group did their warm-up program. The kinematic variable in a cutting maneuver was measured using VICON motion analysis and ankle and knees’ pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In their research, Sidi et al (2023) examined the effect of an eight-week FIFA 11 + training program on knee kinematics and proprioception of male and female soccer players. The results of this research indicated that knee proprioception and valgus angle improved after applying the exercise protocol [24]. The similarity of training research's program this the current research can may be one of the reasons for its alignment.…”
Section: Discussionmentioning
confidence: 54%
“…In their research, Sidi et al (2023) examined the effect of an eight-week FIFA 11 + training program on knee kinematics and proprioception of male and female soccer players. The results of this research indicated that knee proprioception and valgus angle improved after applying the exercise protocol [24]. The similarity of training research's program this the current research can may be one of the reasons for its alignment.…”
Section: Discussionmentioning
confidence: 54%
“…Finally, it should be noted that hip and thigh strength are just one component when it comes to lower extremity injuries. Prior research has found flexibility, proprioception, and kinematics to also be important factors when evaluating lower extremity injuries 59–61 …”
Section: Limitationsmentioning
confidence: 99%
“…At rest or in a static-state, joints are stabilized by the connective tissue and ligaments that surround them in conjunction with overlying muscle [6]. In this state, the connective tissue remains relatively stiff and supports the joints, but when a subject begins to exercise and the heat of physical activity (dynamic state) warms up connective tissue [7] [8], including fascia layers, the support afforded by connective tissue around joints is replaced by that of muscle tissue.…”
Section: Introductionmentioning
confidence: 99%